2009
DOI: 10.1177/0363546509351481
|View full text |Cite
|
Sign up to set email alerts
|

Knee-to-Ankle Mosaicplasty for the Treatment of Osteochondral Lesions of the Ankle Joint

Abstract: Indications for mosaicplasty with a plug transfer from the knee to the talus must be considered carefully, as at midterm, moderate outcome and considerable donor-site morbidity may be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
217
6
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(236 citation statements)
references
References 48 publications
10
217
6
3
Order By: Relevance
“…458 Both can lead to satisfactory clinical results, but disadvantages include donor site morbidity in up to 50%, talar surface mismatching, and limited availability. 122,343,407 Furthermore, recurrent lesions, cartilage degeneration, and discontinuity of the subchondral bone plate have been observed aft er osteochondral autograft transfer, 407 as well as inferior results in the treatment of secondary OCDs. 193 Autologous chondrocyte implantation is another alternative but involves two surgical procedures and is more suitable for superfi cial cartilage defects than for cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…458 Both can lead to satisfactory clinical results, but disadvantages include donor site morbidity in up to 50%, talar surface mismatching, and limited availability. 122,343,407 Furthermore, recurrent lesions, cartilage degeneration, and discontinuity of the subchondral bone plate have been observed aft er osteochondral autograft transfer, 407 as well as inferior results in the treatment of secondary OCDs. 193 Autologous chondrocyte implantation is another alternative but involves two surgical procedures and is more suitable for superfi cial cartilage defects than for cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage of OATS is the donor-site morbidity, which has been reported to occur in up to 50% of cases. 312,327,407 Allograft transplantation has gained increased attention as an alternative for large OCDs in the United States. El-Rashidy et al and Haene et al reported satisfactory outcomes after a mean follow-up of 3 to 4 years.…”
Section: Part III -Secondary Surgical Treatment With a Metal Resurfacmentioning
confidence: 99%
See 1 more Smart Citation
“…Gül et al [70] also reported that the clinical outcomes following AOT with subchondral cyst formation were as successful as those without a subchondral cyst. Donor site morbidity is also a concern in some series [71]. More recent studies, however, demonstrated that OLT treated with AOT have a low incidence of donor site morbidity with good functional outcomes.…”
Section: Replacement Procedures Autologous Osteochondral Transplantationmentioning
confidence: 99%
“…It has proven to be delicate because of the incongruency of the donor-and recipient site and is associated with high donor-site morbidity. In more than 50% of the cases, complaints in the knee joint from where the grafts were harvested have been reported [31]. Furthermore, an autograft cannot be implanted in the ankle without an osteotomy of the medial or lateral malleolus, which can lead to future complications and late adverse effects already described above.…”
Section: Cartilage Reconstructionmentioning
confidence: 99%